2014
DOI: 10.4103/1658-354x.144083
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of adding dexamethasone, midazolam, or epinephrine to 0.5% bupivacaine in supraclavicular brachial plexus block

Abstract: Aims:The aim was to assess the effectiveness of adding either dexamethasone or midazolam in comparison with epinephrine addition to 0.5% bupivacaine in supraclavicular brachial plexus block.Settings and Design:This is a prospective randomized controlled observer-blinded study.Subjects and Methods:This study was carried out in Tanta University Hospital on 60 patients of both sexes; American Society of Anesthesiologists physical Status I and II, age range from 18 to 45 years undergo elective surgery to upper lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 16 publications
3
9
0
Order By: Relevance
“…Many additives are used to improve the quality of analgesics, but the results are either uncertain or associated with undesirable adverse effects [1]. This study revealed that the addition of midazolam to bupivacaine during ultrasound-guided supraclavicular BPB provided better neurological and analgesic qualities than the addition of neostigmine.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Many additives are used to improve the quality of analgesics, but the results are either uncertain or associated with undesirable adverse effects [1]. This study revealed that the addition of midazolam to bupivacaine during ultrasound-guided supraclavicular BPB provided better neurological and analgesic qualities than the addition of neostigmine.…”
Section: Discussionmentioning
confidence: 98%
“…It prevents the undesirable effects of using general anesthesia and upper airway instruments [1]. Moreover, it reduces the duration of hospitalization and costs, and provides complete muscle relaxation [1, 2]. The ultrasound-guided technique requires a lower anesthetic volume to provide an efficient block and decreases the risk associated with intravascular injections and trauma to the surrounding tissues [3].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations